GGA and Meta-GGA study of electronic, optical and thermoelectric properties of fluorinated borophene. (July 2020) - Fakhrabad, Davoud Vahedi; Yeganeh, Mahboubeh
Abstract: In this study, electronic, thermoelectric and optical properties of partially fluorinated borophene were investigated in the framework of density functional theory. The calculations performed by standard generalized gradient approximation (GGA) as well as meta -GGA. The bandgap energy increased from 0.4 eV by GGA to 0.87 eV in the case of meta -GGA. Thermoelectric property investigations revealed the figure of merit close to unity while the thermoelectric performance of the monolayer improved by meta -GGA calculations. The real and imaginary parts of the dielectric function exhibited optical anisotropic behaviors. Highlights: Electronic, optical & TE properties of B2 F monolayer were investigated by DFT through PBE and TB09 functional. Band gap energy increased to 0.87 eV when the meta-GGA-TB09 was used. The quality of B2 F for TE applications were estimated by dimensionless figure of merit as a function of chemical potential. The B2 F monolayer showed optical anisotropic behavior while having absorption edge in mid/near infrared and visible region.